India's Pakistan Policy : How Think Tanks are Shaping Foreign Relations - Bhatnagar, Stuti (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book critically examines the role of think tanks as foreign policy actors. It looks at the origins and development of foreign policy think tanks in India and their changing relevance and position as agents within the policy making process. The book uses a comparative framework and explores the research discourse of prominent Indian think tanks particularly on the India-Pakistan dispute and offers unique insights and perspectives on their research design and methodology. It draws attention to the policy discourse of think tanks during the Composite Dialogue peace process between India and Pakistan and the subsequent support from the government which further expanded their role. One of the first books to offer empirical analyses into the role of these bodies in India, this book highlights the relevance of and the crucial role that these institutions have played as non-state policy actors. Insightful and topical, this book will be of interest to researchers focused on international relations, foreign policy analysis and South Asian politics. It would also be a good resource for students interested in a theoretical understanding of foreign policy institutions in general and Indian foreign policy in particular"--
Introduction -- Think tanks and foreign policy : a discursive institutionalist-Gramscian approach -- Think tanks and Indian foreign policy : an overview -- Government think tanks : promoting security centred government narratives on Pakistan -- Non-government policy think tanks -- Peacebuilding think tanks -- Foreign policy think tanks : challenging or building consensus on India's Pakistan policy.
Includes bibliographical references and index.
Keywords: Research institutes -- India; India -- Foreign relations -- Pakistan; Pakistan -- Foreign relations -- India